Pemberdayaan Karang Taruna HIMUBORA melalui Pupuk Fermentation dan Granulation System - Vierina Beta Nurintan; Nita Ernawati; Rizki Dandy Maulana Putra; Fajar Pradana; Entry Widyawati Kusuma (IKIP PGRI Bojonegoro, 2019)
ABSTRACT The problem in Bocek Krajan village is the presence of organic waste like vegetables and fruits leftover that are left to rot without any special treatment. In addition there is livestock manure waste like urine or feces and tofu water waste from the tofu processing industry that is close to the civil residence. That kind of things that cause foul odors and environmental pollution around the Bocek Krajan Village. This encourages training in the manufacture of fermentation and granuation fertilizer by involving HIMUBORA youth organizations to improve the productivity of youth organizations by implementing agrocomplex waste management systems through fermentation and granulation so as to realize sustainable agriculture and overcome environmental problems. The method used in this activity is a training method. The results of this activity are orbanic waste in the form of leftover vegetables and fruit, as well as waste water of tofu, and livestock manure can be used as liquid fertilizer and granules Keywords: Waste, Fermentation, granuationABSTRAK Permasalahan pada Desa Bocek Krajan yaitu adanya limbah organik seperti sisa sayur dan buah yang dibiarkan membusuk tanpa ada perlakuan khusus. Selain itu terdapat limbah kotoran ternak seperti urin atau feses dan limbah air tahu dari industri pengolahan tahu yang dekat dengan tempat tinggal warga. Hal-hal tersebut menimbulkan bau busuk dan pencemaran lingkungan sekitar Desa Bocek Krajan. Hal ini yang mendorong adanya kegiatan pelatihan pembuatan pupuk fermentation dan granuation dengan melibatkan pemuda karang taruna HIMUBORA guna meningkatkan produktifitas karang taruna dengan penerapan sistem pengelolaan limbah agrokompleks melalui fermentation dan granulation sehingga bisa mewujudkan suistainable agriculture serta mengatasi permasalahan lingkungan. Metode yang digunakan dalam kegiatan ini berupa metode pelatihan. Hasil dari kegiatan ini adalah limbah orbanik berupa sisa sayur dan buah, serta limbah air tahu, dan kotoran ternak dapat dimanfaatkan sebagai pupuk cair dan granul. Kata Kunci: Limbah, Fermentation, granuation